Vegetative and management assessment of restored California coastal grasslands - Justin C Luong (PANGAEA, 2022)
These data are data from vegetation surveys completed at restored California coastal grasslands from 2019-2021 as well as summarized qualitative data from management interviews with restoration practitioners from the corresponding sites. Vegetative data were taken within several 50-m transects using quarter-meter squared quadrats (11 per transect) at each site. Qualitative social data were acquired with management interviews and then summarized as percentages or counts. All data were taken with approval from the UC Santa Cruz Instituional Review Board (IRB). Site names were anonymized as mandated by the IRB.